The Impact of Monetary Policy Communication in an Emerging Economy : The Case of Indonesia - Ahokpossi, Calixte (IMF Working Papers; Working Paper, 2020)
Since the adoption of the inflation targeting framework by Bank Indonesia (BI), monetary policy communication has played an increasingly important role in BI's policy toolkit. This paper assesses BI's monetary policy communication from three perspectives: i) its transparency and clarity, ii) its ability to align market expectation and BI's policy decisions (predictability), and iii) its impact on financial markets. In particular, we assess the impact of BI's monetary policy practices by focusing on its monetary policy press releases and monetary policy reports. The results show that Bank Indonesia has made significant progress in the transparency of its communication as well as in the institutional framework to support this. Nonetheless, the results also suggest ways in which the impact of communication can be further improved, including by strengthening the clarity of policy messages, its consistency with the policy framework and the depth of the money market.